Lighting up sugars: fluorescent BODIPY–gluco-furanose and –septanose conjugates linked by direct B–O–C bonds. Issue 23 (20th May 2016) - Liu, Bowen; Novikova, Nina; Simpson, M. Cather; Timmer, Mattie S. M.; Stocker, Bridget L.; Söhnel, Tilo; Ware, David C.; Brothers, Penelope J.
Abstract : O -BODIPY–glucose conjugates are linked through covalent B–O–C(glucose) bonds, and feature a rare instance of the unnatural septanose form of glucose. Abstract : We report the first O -BODIPY–glucose conjugates, in which the sugar is directly attached to the BODIPY boron through covalent B–O–C bonds. The reaction of Cl -BODIPY with glucose in acetonitrile produced the 1 : 1 α-glucofuranose BODIPY (1 ), 1 : 2 α-glucofuranose BODIPY (2 ) and 1 : 2 α-glucoseptanose BODIPY (3 ) esters. Compound3 is a rare instance of the unnatural septanose form of glucose, and the first example of a septanose borate.